2019
DOI: 10.1021/acsami.9b04169
|View full text |Cite
|
Sign up to set email alerts
|

Alloying and Embedding of Cu-Core/Ag-Shell Nanowires for Ultrastable Stretchable and Transparent Electrodes

Abstract: In this paper, transparent electrodes with dense Cu@Ag alloy nanowires embedded in the stretchable substrates are successfully fabricated by a high-intensity pulsed light (HIPL) technique within one step. The intense light energy not only induces rapid mutual dissolution between the Cu core and the Ag shell to form dense Cu@Ag alloy nanowires but also embeds the newly formed alloy nanowires into the stretchable substrates. The combination of alloy nanowires and embedded structures greatly improve the thermal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…In contrast, Zhang et al demonstrated TSCs with Ag acting as the shell overtop of Cu‐core nanowires and depositing it via spray coating onto a polyurethane (PU) substrate 73. High‐intensity pulsed light (HIPL) both embedded the alloyed nanowires into the PU surface and made them smoother and denser (Figure 3d).…”
Section: Materials For Tscs Based On Nanomaterialsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, Zhang et al demonstrated TSCs with Ag acting as the shell overtop of Cu‐core nanowires and depositing it via spray coating onto a polyurethane (PU) substrate 73. High‐intensity pulsed light (HIPL) both embedded the alloyed nanowires into the PU surface and made them smoother and denser (Figure 3d).…”
Section: Materials For Tscs Based On Nanomaterialsmentioning
confidence: 99%
“…d) Schematic illustration of synthesis process of Cu@Ag core–shell nanowire based nanocomposite. Reproduced with permission 73. Copyright 2019, American Chemical Society.…”
Section: Materials For Tscs Based On Nanomaterialsmentioning
confidence: 99%
See 3 more Smart Citations